2011
DOI: 10.1103/physrevb.84.064127
|View full text |Cite
|
Sign up to set email alerts
|

Series of phase transitions in cesium azide under high pressure studied byin situx-ray diffraction

Abstract: In situ X-ray diffraction measurements of cesium azide (CsN 3) were performed at high pressures up to 55.4 GPa at room temperature. Three phase transitions were revealed as follows: tetragonal (I4/mcm, Phase II) → monoclinic (C2/m, Phase III) → monoclinic (P2 1 /m or P2 1 , Phase IV) → triclinic (P1 or P 1 , Phase V), at 0.5 GPa, 4.4 GPa, and 15.4 GPa, respectively. During the II-III phase transition, CsN 3 keeps its layered structure; and the azide anions rotate obviously. The compressibility of Phase II is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
66
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 37 publications
4
66
0
Order By: Relevance
“…Actually, at 13.6 GPa, Raman spectra10 have identified a phase transition that completes at 32.2 GPa, which is in agreement with the C 2/ m phase being stable above 22 GPa. The I 4/ mcm - C 2/ m sequence has also been observed in CsN 3 11. During I 4/ mcm - C 2/ m transition, the tetragonal lattice is distorted under pressure, and the orientation of anions changes between the two K layers.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Actually, at 13.6 GPa, Raman spectra10 have identified a phase transition that completes at 32.2 GPa, which is in agreement with the C 2/ m phase being stable above 22 GPa. The I 4/ mcm - C 2/ m sequence has also been observed in CsN 3 11. During I 4/ mcm - C 2/ m transition, the tetragonal lattice is distorted under pressure, and the orientation of anions changes between the two K layers.…”
Section: Resultsmentioning
confidence: 70%
“…Lithium azide, which is isostructural to the low-temperature phase of NaN 3 at ambient condition, is stable up to the pressure of 60 GPa at room temperature7. Recent high-pressure study of CsN 3 up to 55.4 GPa reveals three phase transitions approximately at 0.5, 4.4, and 15.4 GPa11. Strikingly, theoretical studies have predicted polymerization of nitrogen in LiN 3 1415 and NaN 3 16.…”
mentioning
confidence: 99%
“…This result is well agreement with the computational bulk modulus K OT ¼ 26.34 GPa with K OT ' ¼ 3.6. 25 In comparison with our previous study on metal azides, the bulk modulus of NH 4 N 3 is softer than heavy metal azides (AgN 3 (39 GPa)) 11 and harder than alkali metal azides (NaN 3 (17.3 GPa), 13 KN 3 (18.6 GPa), 32 CsN 3 (18 GPa) 10 ).…”
mentioning
confidence: 87%
“…5,6 Previous studies indicated that inorganic azides undergo a variety of phase transitions, accompanied by the lattice distortion and reorientation of linear azide anions (N 3 À ) during the temperature or pressure induced phase transitions. [7][8][9][10][11][12][13] High-pressure study on inorganic azides has become an interest topic due to the polymerization of azide anions (N 3 À ) can form a high energy density material under high pressure. Polymerization of nitrogen net is pioneered by studies of nitrogen, a phenomenon which was first predicted in 1985 14 and recently achieved.…”
mentioning
confidence: 99%
“…3 properties of alkali azides also present abundant changes as explored by experimental and theoretical high-pressure studies. [11][12][13][14][15][16][17][18][19] Since a comparison of the high-pressure behaviors of these substances would enable an understanding of the mechanism of pressure-induced phase transitions as well as the evolution of azide ions which might 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 4 result in the formation of polymeric nitrogen. …”
mentioning
confidence: 99%